Levcromakalim, an Adenosine Triphosphate‐Sensitive Potassium Channel Opener, Dilates Extracerebral but not Cerebral Arteries. Issue 9 (18th September 2019) - Al‐Karagholi, Mohammad Al‐Mahdi; Ghanizada, Hashmat; Hansen, Jakob M.; Skovgaard, Lene T.; Olesen, Jes; Larsson, Henrik B. W.; Amin, Faisal M.; Ashina, Messoud
Abstract : Background: ATP‐sensitive potassium (KATP ) channel opener levcromakalim induces migraine attacks in migraine patients. Underlying mechanisms responsible for headache and migraine induction after levcromakalim infusion are unknown. Objective: To investigate the effect of levcromakalim on the cranial arteries and to explore the possible relationship between the middle meningeal artery (MMA) dilation and headache. Methods: In a double‐blind, randomized, placebo‐controlled study, 20 healthy volunteers were scanned at the baseline and repeatedly after infusion of levcromakalim (n = 14) and placebo (n = 6). All participants received a subcutaneous injection of sumatriptan 6 mg before the last scanning. Results: The MMA circumference was significantly larger after levcromakalim compared with placebo ( P  < .0001). The MMA dilation lasted over 5 hours during observational period. We found a significant association between headache and MMA dilation ( P  < .0001). The superficial temporal artery (STA) circumference was significantly larger after levcromakalim compared with placebo ( P  = .03) over the initial period (110 minutes). Over the entire observational period, there was no difference in circumference of the STA and the middle cerebral artery (MCA) between levcromakalim and placebo. Conclusion: Levcromakalim dilated the MMA but not MCA. The MMA dilation was associated with headache. Future studies should investigate whether opening of KATP channels can activate and sensitize the perivascular nociceptors.